Modeling Focused Ultrasound Exposure for the Optimal Control of Thermal Dose Distribution - E. Sassaroli; K. C. P. Li; B. E. O'Neill (The Scientific World Journal)
Preclinical studies indicate that focused ultrasound at exposure conditions close to the threshold for thermal damage can increase drug delivery at the focal region. Although these results are promising, the optimal control of temperature still remains a challenge. To address this issue, computer-simulated ultrasound treatments have been performed. When the treatments are delivered without taking into account the cooling effect exerted by the blood flow, the resulting thermal dose is highly variable with regions of thermal damage, regions of underdosage close to the vessels, and areas in between these two extremes. When the power deposition is adjusted so that the peak thermal dose remains close to the threshold for thermal damage, the thermal dose is more uniformly distributed but under-dosage is still visible around the thermally significant vessels. The results of these simulations suggest that, for focused ultrasound, as for other delivery methods, the only way to control temperature is to adjust the average energy deposition to compensate for the presence of thermally significant vessels in the target area. By doing this, we have shown that it is possible to reduce the temperature heterogeneity observed in focused ultrasound thermal treatments.